Endoscopic treatment options for cholangiocarcinoma. (April 2014) - Hou, Linda Ann; Van Dam, Jacques
SUMMARY  Cholangiocarcinomas are often locally advanced or have metastasized, and at the time of diagnosis individuals often have a poor prognosis. Endoscopic treatment options traditionally include biliary decompression via stenting to allow for systemic chemotherapy and radiotherapy, with self-expanding metal biliary stents being preferred. Recent developments in locoregional therapy delivered endoscopically, such as photodynamic therapy and radiofrequency abalation, have shown promising results in improving patient survival.